The Effect of Coworker Support on Turnover: Role of Job Stress, Organizational Embeddedness, Political Ineptness, and Despotic Leadership - Fadhira, Amalia Dhiaz; Suyono, Joko (Program Studi S3 Ilmu Manajemen, 2024)
This study aimed to examine the topic of the effect of coworker support on employee turnover intention by involving other antecedents namely job stress, organizational embeddedness, political ineptness, and despotic leadership. Two mediating variables are used in this study namely job stress and organizational attachment. In addition, the two moderating variables in this study are political ineptness and despotic leadership. Using a quantitative approach, this study utilized a four-point Likert scale to measure the questionnaire in a cross-section method via snowball sampling on primary data. A total of 323 data were processed using Partial Least Square-Structural Equation Modeling (PLS-SEM) method in SmartPLS software application. The result shows that coworker support has an influence on employee’s desire to leave and change jobs, both through moderating and mediating variables.